Development and validation of an HPLC method for the quantification of a cytotoxic dihydropyranoxanthone in biodegradable nanoparticles - Paiva, AM (2013)
Context and purpose 3,4-dihydro-12-hydroxy-2,2-dimethyl-2H(6Hi-pyrano[3,2-b]xanthen-6-one (compound 1) is a cytotoxic dihydropyranoxanthone exhibiting antiproliferative effects, inducing S-phase cell cycle arrest, and increasing the percentage of apoptotic cells in leukemia cell lines. Nevertheless, the poor aqueous solubility of compound 1 is a major drawback not only for its potential use in therapy but even for the in vitro assessment of its biological activity. Polymeric nanoparticles formulations were developed as potential carriers to overcome problems related with low water solubility of compound 1. The objective of this work was to develop and validate a specific, sensitive and simple HPLC method for the quantitative analysis of the prenylated xanthone (compound 1), which was entrapped in PLGA nanoparticles for the first time. Main findings Chromatographic separation was performed with a reversed-phase C18 column, using methanol: water (85:15, v/v) containing 1 % (v/v) acetic acid as a mobile phase at a flow rate of 1 ml/min and quantification was made by UV detection at 254 nm. The isocratic system required 10 minutes of chromatographic run. The method was shown to be linear (r> 0.999) over the concentration range of 0.50-3.00 pg/ml and precise at the intra-day and inter-day levels as reflected by the relative standard deviation values (lower than 1.5% and 1.6%, respectively). The mean recovery ranged from 97.53 to 104.28 % (RSD: 0.027%) and from 98.49 to 101.81% (RSD: 0.019 %) for nanospheres and nanocapsules, respectively. Brief summary and potential implications A simple, linear, sensitive, accurate, and precise HPLC method suitable for the quantification of compound 1 incorporated in polymeric nanoparticles was developed and validated.